(μ-Butane-1,2,3,4-tetracarboxylato)bis[triaqua(1,10-phenanthroline)nickel(II)] hexahydrate - Hong-lin Zhu (Acta Crystallographica Section E, 2010)
The asymmetric unit of the title compound, [Ni2(C8H6O8)(C12H8N2)2(H2O)6]·6H2O, contains a half of the centrosymmetric dinuclear complex molecule and three uncoordinated water molecules. In the dinuclear molecule, two NiII cations are bridged by the butane-1,2,3,4-tetracarboxylate (BTC4−) anion. Each NiII atom is coordinated by two N atoms from the 1,10-phenanthroline ligand, one O atom from the BTC4− anion and three aqua ligands in a distorted octahedral geometry. Intermolecuar O—H...O hydrogen bonds and π–π stacking interations [centroid–centroid distances = 3.646 (2), 3.781 (2) and 3.642 (2) Å] consolidate the crystal packing.